2016
DOI: 10.18632/oncotarget.9296
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic potential of somatostatin analog SOM230: Indirect pharmacological targeting of pancreatic cancer-associated fibroblasts

Abstract: Pancreatic ductal adenocarcinoma (PDA) shows a rich stroma where cancer-associated fibroblasts (CAFs) represent the major cell type. CAFs are master secretors of proteins with pro-tumor features. CAF targeting remains a promising challenge for PDA, a devastating disease where treatments focusing on cancer cells have failed. We previously introduced a novel pharmacological CAF-targeting approach using the somatostatin analog SOM230 (pasireotide) that inhibits protein synthesis in CAFs, and subsequent chemoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…This finding, although in contrast with the effect of highdose pasireotide in increasing protein synthesis reported in this study, is in line with the previously demonstrated role of SSAs in the inhibition of mTOR and its effectors p70/ S6K and 4E-BP1 in different cell models [6,8]. Therefore, as suggested by the Authors, the Akt-mTOR pathway does not seem to be involved in the pasireotide-mediated anabolic effects, and other signaling cascades could mediate this drug-related activity.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…This finding, although in contrast with the effect of highdose pasireotide in increasing protein synthesis reported in this study, is in line with the previously demonstrated role of SSAs in the inhibition of mTOR and its effectors p70/ S6K and 4E-BP1 in different cell models [6,8]. Therefore, as suggested by the Authors, the Akt-mTOR pathway does not seem to be involved in the pasireotide-mediated anabolic effects, and other signaling cascades could mediate this drug-related activity.…”
supporting
confidence: 92%
“…However, despite the initial search for a compound able to closely mimicking native somatostatin (SRIF-14), preclinical studies have demonstrated that this compound shows different functional properties compared to both native somatostatin-14 and first-generation somatostatin analogs (SSA) (e.g., octreotide) [4]. In this context, due to the peculiar pharmacological characteristics of pasireotide, a number of studies investigated its potential role on extra-pituitary cell types and tissues [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The human orthologue SAA1 was overexpressed in CAFs of patients with PDA and correlated with worse prognosis indicating a potential novel therapeutic target 81. Another interesting study from Bousquet and colleagues in Toulouse recently showed that selective pharmacological activation of somatostatin receptors in CAFs blocks the mTOR/4E-BP1 pathway and subsequent synthesis of several CAF-derived secreted proteins,82 including IL-6 that resulted in sensitisation to gemcitabine and inhibition of cancer cell metastasis 90…”
Section: Introductionmentioning
confidence: 99%
“…In several tumors, stromal cancer-associated fibroblasts (CAF) have a main role in cancer progression and in the development of chemoresistance via the secretion of growth factors and immune suppressive cytokines, mesenchymal-epithelial cell interactions and generation of specific niches within the tumor microenvironment that facilitate the acquisition of drug resistance (Wang et al 2017). In pancreatic adenocarcinoma, pasireotide showed a significant antitumor activity through an effect on CAF (Moatassim-Billah et al 2016). Exclusively, pasireotide, and not octreotide, was able to inhibit in vitro CAF tumorigenic features.…”
Section: Pasireotide Plus Chemotherapymentioning
confidence: 99%